2022
DOI: 10.3389/fimmu.2022.874863
|View full text |Cite
|
Sign up to set email alerts
|

An OGT-STAT5 Axis in Regulatory T Cells Controls Energy and Iron Metabolism

Abstract: The immunosuppressive regulatory T (Treg) cells exert emerging effects on adipose tissue homeostasis and systemic metabolism. However, the metabolic regulation and effector mechanisms of Treg cells in coping with obesogenic insults are not fully understood. We have previously established an indispensable role of the O-linked N-Acetylglucosamine (O-GlcNAc) signaling in maintaining Treg cell identity and promoting Treg suppressor function, via STAT5 O-GlcNAcylation and activation. Here, we investigate the O-GlcN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…6i) 63,64 . Other transcription factors, including STAT5A, and cAMPinducible factors, such as CREB1 and CEBPB, which were related to metabolic fitness of Tregs 65,66 , might ensure functional specialization of Tregs in the NPC microenvironment (Fig. 6i).…”
Section: Mitochondrial Integrity Cholesterol Homeostasis and Fatty Ac...mentioning
confidence: 99%
“…6i) 63,64 . Other transcription factors, including STAT5A, and cAMPinducible factors, such as CREB1 and CEBPB, which were related to metabolic fitness of Tregs 65,66 , might ensure functional specialization of Tregs in the NPC microenvironment (Fig. 6i).…”
Section: Mitochondrial Integrity Cholesterol Homeostasis and Fatty Ac...mentioning
confidence: 99%
“…Regulatory T cells (Treg) are immunosuppressive lymphocytes that control self-tolerance, in ammatory response, and tissue homeostasis. Study has indicated that Treg cell activation can inhibit fatty acid uptake in adipose tissue and reshape systemic iron metabolism [45]. Monocytes are a crucial component of innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…O-GlcNAcylation was also shown to be essential for lineage stability and T cell suppressive function in Treg cells. TCR-induced O-GlcNAcylation was shown to stabilize FOXP3 and activate STAT5 ( 15 ), as well as regulate insulin sensitivity and iron metabolism in Treg cells in a STAT5-dependent manner ( 89 ). Like Treg cells, MSC are also involved in suppressing T cells to maintain homeostasis.…”
Section: O-glcnacylation and Immunometabolismmentioning
confidence: 99%